CULTUROLOGICAL ASPECTS OF ALIEN HYSTERIA. IMAGES OF ALIENS IN MOVIE MYTHS AND LEGENDS - Романчук, Любов; Дябіна, Владислава; Щитов, Дмитро (SWorldJournal, 2023)
The origins and reasons (psychological, religious, social, political, etc.) of the emergence and evolution of the alien myth are analyzed. The images of aliens, depending on their goals and intentions, in various types of art are considered and systematiz